PENYELESAIAN SENGKETA ANTARA PEKERJA DAN PERUSAHAAN TENTANG HAK ATAS INFORMASI - Izza Hasna Fuada (STIH Putri Maharaja, 2020)
The Disputes between employees of PT. Pos Indonesia (Persero) and PT. Pos Indonesia (Persero) Regional II Padang were happened by the failure of workers in the selection to be Head of Subdivision Post Office, in particular with the medical test. The dispute unfortunately was also escalated by the request for information disclosure which is not granted by the committee. The study aims to is address on the question on how to resolve disputes between workers and companies about the right to information on the final recruitment’s selection of employees in particular with PT. Pos Indonesia (Persero) Intake Program Diploma III (D-III) for head of subdivision in the post office. Aside of that, the author also would like to know whether the legal consequences of the central information commission’s decision number: 1356/KIP-PS-A-M/2014 in resolving disputes between workers and companies on the right to information. By using the empirical juridical methods, the result shows that the dispute between workers and PT. Pos Indonesia (Persero) companies Regional II Padang can be settled by the Central Information Commission on Mediation and public information is a right for public as also regulated in Law No. 14 of 2008 concerning Public Information Openness.